THE DETERMINANTS OF INFLATION IN INDONESIA: PARTIAL ADJUSTMENT MODEL APPROACH - Yosefina Don Sama Lelo (Universitas Muhammadiyah Yogyakarta, 2018)
Inflation is one of the economic issues that always being targeted by the government, particularly central bank because it could adversely influence the economy. For the past view years, the inflation targeting framework as the part of monetary policy has been successfully implemented where the interest rate is the operational target. In view of past investigations, there are fundamental factors that affect inflation, for example, interest rate, exchange rate, and money supply. This study aims to evaluate the impact of those factors on inflation both in the short and long run. The estimation uses monthly data from January 2013 to November 2017, which was obtained from Indonesian Banking statistics. The use of Partial Adjustment Model illustrates how interest rates, exchange rate, and money supply negatively and significantly affect inflation on both short and long run. This regression result is consistent with the finding of previous studies which strengthen the evidence that the government should maintain the inflation rate through those variables.